Posterior vaginal compartment repairs: Does vaginal vault (level I) fixation significantly improve the vaginal introital (level III) repair?. Issue 8 (4th July 2018) - Haylen, Bernard T.; Wong, Audris; Kerr, Stephen
Abstract : Introduction: Limited data exist associating vaginal vault and introital defects before and after posterior repairs (PR). We hypothesize: (i) a positive association between the size of vaginal vault and introital defects preoperatively; and (ii) a positive association between the reduction of these defects postoperatively if vault fixation (sacrospinous colpopexy—SSC) is used with the PR. Methods: In a cross‐sectional study of 300 consecutive PRs, the following were measured pre‐ and immediately postoperatively: (i) from POP‐Q: genital hiatus (GH—Level III); (ii) from PR‐Q: perineal gap (PG—Level III), posterior vaginal vault descent (PVVD—Level I). The data for introital defects (GH, PG) were separated according to the need for vault fixation using a SSC due to a larger vaginal defect (PVVD over 5 cm). Results: Mean (SD) preoperative GH and PG were both significantly larger in the SSC versus no SSC group: GH (3.73 [0.94] vs 3.36 [0.83] cm, P = 0.01); PG (2.91 [1.0] vs 2.61 [0.91] cm, P = 0.05). SSC performed with the PR (84%); not performed (16%) cases. The mean (SD) postoperative reduction in GH (antero‐posterior) was significantly (29% —P = 0.002) greater—1.1 (0.69) cm (29.5%) in the SSC group and 0.77 (0.49) cm (22.9%) in the no SSC group. The decrease in the PG (transverse) was greater by 11% (0.05). Conclusions: Levels I and III defects are associated with PRs; preoperatively larger vaginal vault (PVVD over 5 cm) and larger introital defects (GH, PG). Postoperatively, vault fixation resulted in significantly greater reduction in the introital defects. Summary: Vaginal vault fixation (SSC) significantly improves the vaginal introital repair.